Filsafat Manusia Dan Implikasinya Terhadap Rumusan Pendidikan Islam - Abdul Mukit (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2020)
As it is known that man is the special creature and the best work of God SWT. In this Qur'an called 'ahsan taqwim' It's called the best work of course because there are some privileges and advantages it has. Since hundreds of centuries ago, many philosophers have spoken and experienced human meaning to be able to explain the elements in it so that they can explain where and for what human beings are. Misconception of man will have fatal consequences in destroying something related to him. This study will try to explain the meaning of humans with its various elements from a philosophical point of view by its various streams. Then the link between the human philosophy and education and how Islam destroys the human philosophy.